Development of a semen collection and cryopreservation method for establishing an ex situ gene bank in wild rabbits - Debnár, Viktória Johanna; Kerekes, Andrea; Torda, Orsolya; Altbäcker, Vilmos; Bodó, Szilárd (Animal welfare, Ethology and Housing Systems (AWETH), 2017)
The aim of study was to develop a reliable semen collection and cryopreservation method for gene banking in European wild rabbit (Oryctolagus cuniculus). The animals were kept in cages individually. The bucks were trained for ejaculation into an artificial vagina. The device is hand-held beneath a dwarf female with the open end pointed in a caudal direction or placed to a phantom prepared from fur of a rex rabbit. The concentration of semen was counted by a Makler chamber. The ratio of motile and fertile sperm cells was determined by Kovacs-Foote staining. The condition of delivery of semen samples to the place of cryopreservation was studied as well. The motility of sperm cells obtained from cooled (16 °C) and diluted samples (Weitze-Tris 1:1), delivered for 2 hours was determined by CASA (Computer Assisted Semen Analysis). Semen samples (at least 50% sperm motility) were cryopreserved using modified Besenfelder’s freezing protocol. The ratio of live sperm cells with competence of fertility were reduced with 27,3% due to cryodamage. The semen freezing technique in wild rabbit resulted same efficacy as in domestic ones.
Keywords: European wild rabbit; semen collection; cryopreservation; ex situ gene bank